Pedunculated Fibroid Mimicking an Ovarian Cancer - Bhattachan, Kabin; Karki, Aruna; Dangal, Ganesh; Kumari Pradhan, Hema; Shrestha, Ranjana (Nepal Journal of Obstetrics and Gynaecology, 2019)
Large myoma may show various type of degenerative change and have alteration of radiological view. Subserosal or pedunculated fibroid with cystic degeneration may mimic complex ovarian mass on radiological imaging. A 34 year female, para one, with normal menstrual period presented with radiological diagnosis of complex adnexal mass and CA 125 value 100 u/ml. Postoperative finding revealed cystic degeneration of pedunculated subserosal fibroid receiving blood supply from adherent omentum. Keywords: Cystic degeneration, pedunculated fibroid, complex ovarian mass.